Road to lab: cobblestone cycling vibrations transferred to the lab - Viellehner, J.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of the study was to provide vibration recommendations for laboratory-based cycling interventions derived from field tests on cobblestones. For that purpose, the vertical accelerations of the front and rear dropouts (points of wheel fixation at the frame) of the bike frame were recorded, with five experienced cyclists riding on cobblestones at different velocities. Lab vibration recommendations are based on the median frequency (34.6 ± 1.2 - 45.6 ± 0.5 Hz), rms of acceleration (5.5 ± 0.3 - 10.2 ± 0.6 g) , peak acceleration (48.5 ± 3.8 g) , mean amplitude (3.6 ± 4.3 - 5.0 ± 6.4 mm) and peak amplitude (69.7 ± 23.4 mm) of the dropouts. For a lab-based approach with vibration plates, the vibration stimulus should be applied (I) to the rear and front dropout, (II) with two different frequencies used for front (36 - 46 Hz) and rear (32 - 39 Hz) (III) and a mean vertical amplitude of 4 mm. The parameters presented provide the basis for vibration-related material testing, motion analysis or physiological performance testing in cycling.